Evaluación de la ejecución presupuestal del programa generación del empleo social inclusivo Trabaja Perú y su influencia en el desarrollo económico de la Región San Martin, periodo 2012 – 2013 - 2014 - Mestanza Vela, Karen Fiorella (2016)
This thesis is titled: Assessment of the Budget Execution Generation of Inclusive Social Work Jobs Peru and its influence on the economic development of the Region San Martin, Period 2012-2014 program aims to determine the influence of the budget execution Inclusive of Generation Social Work Employment Program Peru, in the Economic Development of San Martin Region during the period 2012-2014. This study is responsible investigation of non-experimental, correlational design. Also, the sample consisted of the documentary heritage in the periods 2012, 2013 and 2014, which are held by the Regional Government and the INEI. With the development of the research was reached the following conclusions: similar trend is evident, since in the period 2013 higher rates are presented in terms of budget execution of the Generation Program Inclusive Social Employment Work Peru, which prompted several people have access to decent jobs, also in 2013 the San Martin region, presented an economic growth rate equivalent to 5.01% as per capita income has increased, the number of unemployed people were reduced, and more people econtraron how to access basic services. Thus we can say that the alternative hypothesis (Hi) is correct, since it is evident that the Budget Execution Generation of Inclusive Social Work Employment Program Peru influences the economic development of the Region San Martin, 2012-2014. The implementation of social programs that contribute to the welfare of the general population is related positively with the present economic development in the regiónde San Martin, as it has been shown that many people have improved their quality of life by having a steady job, income that generates frequent